Research on advancing chromatic reproduction and luminosity of a WLED using triple-layer remote phosphor arrangement - Ha Thanh Tung; Huu Phuc Dang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
In this study, the use of triple-sheet phosphor arrangement (TRP) in performing significant improvements to both color quality and luminous flux of white light emitting diode (WLEDs) is introduced. The phosphor layer of CaLaB3O7:Ce3+,Mn2+ is to accomplish green-spectra enhancement for the boost of luminous efficacy (LE), while MgB2O4:Mn2+ red phosphor layer is for red-spectra enhancement to better color rendering index (CRI) of WLEDs. The changes in these two phosphors’ concentrations present considerable effects on the yellow phosphor YAG:Ce3+ concentration, the color quality scale (CQS), CRI, and LE. Findings display the decrease of YAG:Ce3+ concentration accompanying the increase of red and green phosphor concentrations, for the stabilized average correlated color temperatures (ACCTs) between 6000 and 8500 K. Results also reveal that greater content of MgB2O4:Mn2+ leads to greater CRI value. Meanwhile using the increasing CaLaB3O7:Ce3+,Mn2+ concentration, the CRI lowers considerably. CQS, on the other hand, can increase with CaLaB3O7:Ce3+,Mn2+ concentration from 10% to 14%. Especially, given the enhancement for the CRI as well as CQS, LE value will surge to more than 40% due to the reduction of scattering light and the addition of green light. The outcome of the study is a priceless reference for light emitting diode (LED) producers.